2023
DOI: 10.1021/acsami.2c18522
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Structure of Sn/SnO2 Constructed via Phase Engineering for Efficient and Stable CO2 Reduction

Abstract: The electrochemical carbon dioxide reduction reaction (CO 2 RR) catalyzed by Sn-based materials shows great potential for CO 2 -to-formate conversion. The presence of tin species with different oxidation states can promote the catalytic performance, most likely due to the interfaces of metallic and oxide phases that induce a synergistic effect. Therefore, it is desirable yet challenging to synthesize a hybrid catalyst with abundant active heterogeneous interfaces. Herein, we synthesize a hybrid catalyst constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
2
7
0
Order By: Relevance
“…In other words, the oxidation state of tin oxide is one of the key factors that determine the CO 2 RR activity in SnO 2 /ZC catalysts. This inference is in good agreement with the findings of previous reports [41][42][43][44].…”
Section: Resultssupporting
confidence: 94%
“…In other words, the oxidation state of tin oxide is one of the key factors that determine the CO 2 RR activity in SnO 2 /ZC catalysts. This inference is in good agreement with the findings of previous reports [41][42][43][44].…”
Section: Resultssupporting
confidence: 94%
“…There are several reports suggesting the formation of Sn by the reduction of SnO 2 during the electrochemical CO 2 reduction reaction, and the in situ formed Sn/SnO 2 boosts the CO 2 reduction kinetics. 36 For example, Liu et al 70 reported in situ phase engineered Sn/SnO 2 for an efficient and stable CO 2 reduction reaction. Therefore, the increased catalytic activity as well as decrease of the CO 2 reduction potential of (Sn/SnO 2 ) 15 −CN x may be due to the presence of an effective Sn/SnO 2 heterojunction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Meanwhile, the Sn-based materials showed a superior performance for CO 2 conversion to HCOO − , constructing a synergistic effect with ZnO-based materials which enhanced the HCOO − selectivity. [174][175][176] Tan et al 177 presented a SnO 2 /ZnO composite hollow nanofiber (HNF) for eCO 2 RR to HCOOH. By comparing the electrochemical performance and physicalchemical properties of the SnO 2 /ZnO composite HNF with the SnO 2 HNF and SnO 2 NPs, they also found that the SnO 2 /ZnO composite HNF was the most suitable catalyst for the production of HCOOH (Fig.…”
Section: Nanoscale Reviewmentioning
confidence: 99%